Bank liquidity creation and CEO optimism - Huang, Shu-Chun; Chen, Wei-Da; Chen, Yehning (Journal of Financial Intermediation, 2018)
Using U.S. banking data between 1993 and 2014, this paper investigates the relationship between CEO optimism and bank liquidity creation. It finds that banks with optimistic CEOs create more liquidity over the entire sample period. In addition, the positive effect of CEO optimism on liquidity creation became stronger during the subprime crisis of 2007‒2009, and this stronger effect was mainly driven by banks with high capital ratios and large banks. These results imply that CEO optimism is likely to encourage banks to create liquidity, especially during banking crises. The results presented in this paper hold when subjected to various robustness checks.